The Benefits of Regional Conferences in Promoting Scholarship Keynote Address for Southern Criminal Justice Association - Moak, Stacy C. (American journal of criminal justice, 2010)
This manuscript was presented as the keynote address of the Southern Criminal Justice Association annual conference. The keynote addressed several concepts argued to promote successful scholarship in criminal justice and criminology; specifically networking and mentoring. Further, the keynote details the benefit of participation in regional conferences for both academics and students. Finally, it challenges academics and students of all ranks to continue to participate and support regional conferences.